An intermolecular C–H oxidizing strategy to access highly fused carbazole skeletons from simple naphthylamines. Issue 91 (30th October 2019) - Rank, Christian K.; Jones, Alexander W.; Wall, Tatjana; Di Martino-Fumo, Patrick; Schröck, Sarah; Gerhards, Markus; Patureau, Frederic W.
Abstract : Highly π-extended hetero-cyclic/aromatic skeletons are of great importance as they can be utilized in many organic material based technologies. Abstract : Highly π-extended hetero-cyclic/aromatic skeletons are of great importance as they can be utilized in many organic material based technologies. Therefore, developing efficient, pre-activation-free, synthetic procedures for the rapid build-up of these complex structures remains a high priority objective. The herein presented approach delivers highly fused carbazole skeletons from simple naphthylamine derivatives.